Management of Leadership through Extracurricular Activities in Achieving SDGs No. 4 at Al-Rosyid Islamic Boarding School - Laitstin Nafis; Lailya Zahrotun Nabila (CV. Gerasi Insan Nusantara, 2026)
Quality education is not only academic achievement but also the development of character, social skills, and leadership of students. In the context of Islamic boarding schools, extracurricular activities are an important instrument because they take place in a boarding school environment that emphasizes discipline, exemplary behavior, and the instilling of religious values. This study aims to analyze the management of extracurricular activities in the formation of student leadership character and its contribution to the achievement of the Sustainable Development Goals (SDGs), especially SDG 4 on quality education. This study uses a quasi-qualitative method with a phenomenological approach. Data were obtained through in-depth interviews, non-participatory observation, and documentation studies involving Islamic boarding school leaders, teachers, and extracurricular activity documents. Data analysis was carried out through deductive data reduction and thematic analysis. The results of the study indicate that the management of extracurricular activities at Al-Rosyid Islamic Boarding School in Bojonegoro is carried out systematically through the stages of planning, organizing, implementing, monitoring, and evaluating. Scouting, muhadloroh (public speaking groups), discussions, and student organizations have been shown to foster responsibility, discipline, courage, communication skills, and students' readiness to lead and be led. Key supporting factors include the availability of facilities and internal coordination, while the primary constraint lies in limited time. Thus, extracurricular activity management contributes significantly to the development of student leadership character while supporting the achievement of SDG 4 by strengthening skills and character, and creating an effective, inclusive, and sustainable learning environment